Crystal structure of E. coli apolipoprotein N-acyl transferase - Guangyuan Lu (Nature Portfolio, 2017)
Apolipoprotein N-acyl transferase (Lnt) catalyses the final step in the protein lipidation pathway of Gram-negative bacteria. Here, the authors present the crystal structure ofE. coliLnt, which consists of a transmembrane domain and a nitrilase domain localised at the periplasmic side of the membrane.